Targeting of MAD2L1 by miR‐515‐5p involves the regulation of cell cycle arrest and apoptosis of colorectal cancer cells. (2nd March 2022) - Ding, Xiang; Fu, Qingyan; Chen, Weixing; Chen, Linjie; Zeng, Qingjun; Zhang, Sanjun; He, Linfang
Abstract: Although many previous studies have found that the mitotic arrest deficient 2‐like 1 (MAD2L1) protein contributes to the proliferation of colorectal cancer (CRC) cells, but the upstream mechanism of MAD2L1 is still largely elusive. This study aimed to explore the microRNAs (miRNAs) upstream of MAD2L1 to improve our understanding of the mechanism of the MAD2L1 gene in CRC. The upstream target miRNAs (miR‐515‐5p) of MAD2L1 were predicted by the online databases miRWalk, miRDIP, and TargetScan. Quantitative real‐time PCR (qRT‐PCR) was used to detect the expression level of miR‐515‐5p in human CRC tissues. The targeting relationship between miR‐515‐5p and MAD2L1 was tested by dual luciferase reporter gene assays. The effects of miR‐515‐5p on the biological behaviors of CRC cells by regulating MAD2L1 expression were verified by qRT‐PCR, western blot, Cell Counting Kit‐8, and flow cytometry. The results showed that miR‐515‐5p was a highly reliable upstream miRNA of the MAD2L1 gene. As an upstream target miRNA of MAD2L1, miR‐515‐5p was lowly expression in CRC tissues. The overexpression of miR‐515‐5p could inhibit the proliferation of CRC cells and induce cell cycle arrest at the G1 phase leading to cell apoptosis. However, MAD2L1 gene overexpression could reverse the effects of miR‐515‐5p overexpression on the biological behaviors of CRC cells above. This study illustrated that miR‐515‐5p can inhibit proliferation and induce G1 phase arrest leading to apoptosis in CRC cells. The mechanism underlying this phenomenon may be related to the negative targeted regulation of MAD2L1 .